Advanced modality imaging evaluation in acute ischemic stroke may lead to delayed endovascular reperfusion therapy without improvement in clinical outcomes. (16th October 2012) - Sheth, Kevin N; Terry, John B; Nogueira, Raul G; Horev, Anat; Nguyen, Thanh N; Fong, Albert K; Gandhi, Dheeraj; Prabhakaran, Shyam; Wisco, Dolora; Glenn, Brenda A; Tayal, Ashis H; Ludwig, Bryan; et al.
Abstract : Purpose: Advanced neuroimaging techniques may improve patient selection for endovascular stroke treatment but may also delay time to reperfusion. We studied the effect of advanced modality imaging with CT perfusion (CTP) or MRI compared with non-contrast CT (NCT) in a multicenter cohort. Materials and methods: This is a retrospective study of 10 stroke centers who select patients for endovascular treatment using institutional protocols. Approval was obtained from each institution's review board as only de-identified information was used. We collected demographic and radiographic data, selected time intervals, and outcome data. ANOVA was used to compare the groups (NCT vs CTP vs MRI). Binary logistic regression analysis was performed to determine factors associated with a good clinical outcome. Results: 556 patients were analyzed. Mean age was 66±15 years and median National Institutes of Health Stroke Scale score was 18 (IQR 14–22). NCT was used in 286 (51%) patients, CTP in 190 (34%) patients, and MRI in 80 (14%) patients. NCT patients had significantly lower median times to groin puncture (61 min, IQR (40–117)) compared with CTP (114 min, IQR (81–152)) or MRI (124 min, IQR (87–165)). There were no differences in clinical outcomes, hemorrhage rates, or final infarct volumes among the groups. Conclusions: The current retrospective study shows that multimodal imaging may be associated with delays in treatment without reducing hemorrhage rates or improving clinical outcomes. This exploratory analysis suggests that prospective randomised studies are warranted to support the hypothesis that advanced modality imaging is superior to NCT in improving clinical outcomes.